1998
DOI: 10.1152/ajpregu.1998.275.3.r706
|View full text |Cite
|
Sign up to set email alerts
|

The thromboxane A2 mimetic U-46619 inhibits somatomotor activity via a vagal reflex from the lung

Abstract: Vagal reflexes from the heart and lungs elicit autonomic as well as somatomotor responses. The purpose of the present investigation was to determine whether the inflammatory mediator thromboxane A2 inhibits the knee-jerk reflex via a vagally mediated reflex from either the heart or the lung. The thromboxane A2 mimetic U-46619 (0.8 ± 0.08 μg/kg) was injected through a catheter placed near the right atrium ( n = 11), near the aortic arch ( n = 7), or into the pericardial sac ( n = 4) in 11 chloralose-anesthetize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…Our observation that intrapericardial application of U-46619 evokes sympathoexcitatory reflex responses, including increases in arterial pressure and RSNA in sinoaortic denervated and vagotomized animal, contrasts with the results of earlier studies (41,53), which have suggested that intrapericardial U-46619 does not alter peak systolic BP of anesthetized cats, either before or after vagotomy. Although the discrepancies between these earlier studies and our current observation are unclear, it is possible that baroreflex activation may have limited the excitatory cardiovascular response to epicardial U-46619, since these previous investigations did not perform sinoaortic denervation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our observation that intrapericardial application of U-46619 evokes sympathoexcitatory reflex responses, including increases in arterial pressure and RSNA in sinoaortic denervated and vagotomized animal, contrasts with the results of earlier studies (41,53), which have suggested that intrapericardial U-46619 does not alter peak systolic BP of anesthetized cats, either before or after vagotomy. Although the discrepancies between these earlier studies and our current observation are unclear, it is possible that baroreflex activation may have limited the excitatory cardiovascular response to epicardial U-46619, since these previous investigations did not perform sinoaortic denervation.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, exogenous TxA 2 stimulates hindlimb group III and IV afferent nerves (25). Also, the TxA 2 mimetic U-46619 inhibits the knee-jerk reflex through a vagal pathway originating in the lung (41). U-46619 also evokes tachypnea and a depressor reflex response, including bradycardia and hypotension through stimulation of the vagus nerve (7,41,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest report of such an effect was by Schweitzer and Wright [109], who showed that electrical stimulation of the central terminus of the vagal nerve in cats was associated with a reduction in the knee-jerk reflex. Subsequent animal studies showed that activation of vagal afferent nerves to the lungs or to the abdomen caused reflex inhibition of somatomotor activity, including reflex activation of skeletal muscles and exerciseinduced electromyogram activity [110][111][112][113][114][115][116]. Other studies have shown that a variety of substances, such as 5-HT, cytokines, and prostaglandins, can stimulate vagal afferent nerves [117][118][119][120].…”
Section: Vagal Afferent Nerve Activationmentioning
confidence: 99%
“…More recently, activation of vagal afferents by a 5-hydroxytryptamine 3 (5HT3) receptor agonist reduced steady state exercise-induced EMG activity in conscious rats [32]. Intravenous injection of a thromboxane A2 receptor agonist can inhibit the knee-jerk reflex in anesthetized cats [100]. Other studies in the rat have shown that activation of abdominal vagal afferents reduced reflex activation of skeletal muscles [67].…”
Section: The Vagal Afferent Hypothesismentioning
confidence: 99%